(untitled) (World Economics and Finance Bulletin, 2023)
Iraq witnessed many political and economic transformations and aimed to rebuild the destruction caused by the wars. According to the new market mechanisms, Iraq opened the doors to foreign investment and allowed nonIraqi labor to come to Iraq and work in all economic activities. The research aims to clarify the objective reality that the labor market was exposed to in an environment. The Iraqi economy during the period of research and the problems that they faced, i.e., employment in light of the openness of the Iraqi markets and their great openness to global markets and the entry of large numbers of foreign workers, which negatively affected the labor market in the environment of the Iraqi economy. The research started from the hypothesis of economic models witnessed by some countries in In light of the economic prosperity and the increasing increase in the use of labor in light of the development of the productive sectors, which was reflected in the labor market in those countries and the improvement of the living conditions of the working class and the increase in the number of workers as a result of the development of production in those environments, the research sheds light on the course of developments taking place in the Iraqi economy environment in general and the market Work in particular, and what the labor sector was exposed to in light of the economic openness witnessed by the Iraqi economy after 2007, and the most critical actual events that the labor market was exposed to.